2007
DOI: 10.1136/jme.2005.013268
|View full text |Cite
|
Sign up to set email alerts
|

Paternity fraud and compensation for misattributed paternity

Abstract: Claims for reimbursement of child support, the reversal of property settlements and compensation can arise when misattributed paternity is discovered. The ethical justifications for such claims seem to be related to the financial cost of bringing up children, the absence of choice about taking on these expenses, the hard work involved in child rearing, the emotional attachments that are formed with children, the obligation of women to make truthful claims about paternity, and the deception involved in infideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 7 publications
0
22
0
2
Order By: Relevance
“…Babanın bebeğiyle birlikte olması, dokunması, konuşması, oynaması, çocuğuyla ilgili çeşitli kararlara aktif olarak katılması çocuğuyla arasında güçlü bir bağın oluşmasına neden olmakta ve daha sonraki baba çocuk ilişkisinin devamını sağ-lamaktadır. Babası ile bebekliğin ilk günlerinden itibaren iletişimde olan çocukların duygusal, bilişsel ve sosyal becerilerinin diğer çocuklara göre daha güçlü olduğu belirtilmektedir (6)(7)(8)(9)(10)(11) . Baba olmak bir erkeğin yaşamının tüm yönlerinde iz bırakacak nitelikte yaşamında kalıcı değişiklik yaratan bir olaydır.…”
Section: Introductionunclassified
“…Babanın bebeğiyle birlikte olması, dokunması, konuşması, oynaması, çocuğuyla ilgili çeşitli kararlara aktif olarak katılması çocuğuyla arasında güçlü bir bağın oluşmasına neden olmakta ve daha sonraki baba çocuk ilişkisinin devamını sağ-lamaktadır. Babası ile bebekliğin ilk günlerinden itibaren iletişimde olan çocukların duygusal, bilişsel ve sosyal becerilerinin diğer çocuklara göre daha güçlü olduğu belirtilmektedir (6)(7)(8)(9)(10)(11) . Baba olmak bir erkeğin yaşamının tüm yönlerinde iz bırakacak nitelikte yaşamında kalıcı değişiklik yaratan bir olaydır.…”
Section: Introductionunclassified
“…This discrepancy between social or legal paternity and genetic paternity has been described as, 'Parental discrepancy', 'non-paternity event' or 'misattributed paternity'. 1,2 Parental discrepancy may be an incidental discovery in the course of genetic testing for other medical conditions. 3 The parent, particularly the male, may also become apprehensive about his place in the biological make-up of the child whose paternity has been attributed to him and demand for paternity test to ascertain the true parentage (paternity) of the child.…”
Section: Introductionmentioning
confidence: 99%
“…4 Outside the context of assisted reproduction, this situation is assumed to be a definite proof of infidelity. 2 There are both conventional and non-conventional methods of assessing paternity. The nonconventional methods include the possession of certain recognizable physical features of the family of both parents by the child.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] The knowledge of the father in the baby care can make him feel more comfortable about it and allow him to participate more in baby care. [12] Our study indicated that the majority of the fathers in experimental and control groups did not receive baby care training before.…”
Section: * Mwu = Mann Whitney Umentioning
confidence: 99%